How to manage the mind of the reformist movement in building the Muslim community - Hamd Hadi Badn ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
1-That Islam gave great attention to reason and thought, and gave man the freedom to see and think, because if reason and thought looked at the great creation and creation of God, and were stripped of all concerns, it will inevitably lead him to fear of God and his piety, and thus correct his thought of everything that leads him to aberration Deviation and corruption. 2-Islam was deeply concerned with the reform and renewal of thought, and he meant it with great care. Indeed, God Almighty indicated in his book that it is one of the great blessings that he grows with them, so no happiness and tranquility for the individual will be achieved except by its fulfillment. The bliss of the people of paradise is to achieve reform for them by the Almighty saying: (And those who believe and do righteous deeds, so that we may bring them into the righteous).3-That the concept of reform aims to build a civilized society that is far from the attraction that aims to tear the ranks of Muslims, and the law has a vision in preserving religion and reason, and building the concept of intellectual reform calls for reviewing the texts of Islamic law and its applications, to reach an integrated vision to achieve the desired civilization reform to build The human mental system.4-The creation of the concept of reform came at a late stage, and scholars, preachers and reformers in the history of the Islamic nation have had great efforts in seeking to achieve it and strive to preserve the thought of Muslims and address everything that leads them to deviation as previously explained .